Sistem Pendukung Keputusan Kelayakan Pendonor Darah menggunakan Metode Analitical Hierarchy Process di UTD PMI Kota Bengkulu - Gunawan, Sukro Adi; Wahyudi, Jusuf; Rohmawan, Eko Prasetyo (LPPM UNIKA Santo Thomas Medan, 2022)
In this computerized era, agencies need a system that can produce information quickly, accurately, effectively, and efficiently. This system is expected to provide solutions to decision makers in determining the right steps to determine a decision. The use of computerized systems does not only touch the business world but also in the health sector, including the decision-making process for the eligibility of blood donors. Because the decisions made by a PMI officer in blood donation activities will have a major impact on the health of several people concerned, PMI must be very careful in allowing or prohibiting potential blood donors to donate blood. This is the basis of the research. The research is to create a decision support system for PMI officers to be able to decide the eligibility of potential donors. The method used in the decision consideration is the AHP (Analytical Hierarchy Process) method. The results of this study are in the form of a ranking report from the results of the calculation of the AHP method on the value of each criterion.